On the Path to Becoming a Teacher: Student Teachers' Competency in Instructional Planning. Issue 3 (10th August 2021) - Yurtseven, Nihal
Abstract: The purpose of the study is to examine how the student teachers' perceptions of instructional planning competency predict their competency in instructional planning. The study was carried out through explanatory mixed method design. The participants of the study included 102 teacher candidates, 65 of whom were female and 37 of whom were male. As quantitative data collection tools, The Scale for Perception of Proficiency in Instruction Planning (SPPIP) developed by Gülbahar and UbD Design Standards Rubric developed by Wiggins and McTighe were used. As qualitative data collection tools, unit plans and focus group interview were used. The quantitative data was analyzed by applying correlational analysis and simple linear regression analysis. The qualitative data was analyzed through content analysis. The regression analysis demonstrate that student teachers' perceived proficiency in instructional planning explained 57% (R 2 = .57) of the competency in instructional planning. As for the qualitative portion of the study, the analysis of collected data revealed three themes regarding student teachers' views on competency in instructional planning process: factors affecting competency, challenging elements in instructional planning, and strategies to develop competency.